Among Arabic manuscripts : memories of libraries and men - Krachkovskiĭ, I. I︠U︡. 1883-1951. (Brill Classics in Islam, 1953)
I.Y. Kratchkovsky (Ignatii Iul'ianovich Krachkovskii) was an iconic scholar, and Among Arabic Manuscripts, Memories of Libraries and Men gives us a good indication of what made him so outstanding. Hugely influential in its time, especially in Eastern Europe, it inspired several now-noted Arabists to start their studies in this field. It is beautifully written and, with the rising relevance of Arab-Russian relations has new historical importance. A memoir of a life in Orientalism, this autobiographic text is the result of strong will and endurance, and of total dedication to Arabic literature and language. It tells of Kratchkovsky's enormous achievements in the field, in a very personal manner and in an easily accessible form. The present publication is the English translation of the first 1953 Brill edition, accomplished by Tatiana Minorsky (d. 1987), with a new introduction by Michael Kemper.